Limits on manipulating conditional photon statistics via interference of weak lasers - Hong, Kang-Hee; Jung, Jisung; Cho, Young-Wook; Han, Sang-Wook; Moon, Sung; Oh, Kyunghwan; Kim, Yong-Su; Kim, Yoon-Ho (OPTICAL SOC AMER, 2017)
Photon anti-bunching, measured via the Hanbury-Brown-Twiss experiment, is one of the key signatures of quantum light and is tied to sub-Poissonian photon number statistics. Recently, it has been reported that photon anti-bunching or conditional sub-Poissonian photon number statistics can be obtained via second-order interference of mutually incoherent weak lasers and heralding based on photon counting [Phys. Rev. A 92, 033855 (2015); Opt. Express 24, 19574 (2016); https://arxiv.org/abs/1601.08161]. Here, we report theoretical analysis on the limits of manipulating conditional photon statistics via interference of weak lasers. It is shown that conditional photon number statistics can become super-Poissonian in such a scheme. We, however, demonstrate explicitly that it cannot become sub-Poissonian, i.e., photon anti-bunching cannot be obtained in such a scheme. We point out that incorrect results can be obtained if one does not properly account for seemingly negligible higher-order photon number expansions of the coherent state. (C) 2017 Optical Society of America
Keywords: EXPERIMENTAL REALIZATION; GENERATION; COHERENT; STATES; ENTANGLEMENT